The Clinical Utility of Immunoglobulin G4 in the Evaluation of Autoimmune Pancreatitis and Pancreatic Adenocarcinoma - Pak, Linda M. (HPB (Oxford), 2017)
BACKGROUND: Elevation in the serum immunoglobulin-G4 (IgG4) level has been used as a diagnostic marker to distinguish autoimmune pancreatitis (AIP) from pancreatic ductal adenocarcinoma (PDAC), but its true utility is ill-defined. This study evaluates the clinical utility of IgG4 in differentiating AIP from PDAC. METHODS: All patients evaluated in the hepatopancreaticobiliary surgery clinics with measured serum IgG4 were included. Patients were divided into normal IgG4 (<135mg/dL) and elevated IgG4 (≥135mg/dL) groups. The final diagnosis was determined by operative pathology when available or by clinical outcome. The sensitivity, specificity, PPV, and NPV of IgG4 for diagnosing AIP was assessed. RESULTS: Between 1997 and 2015, 298 patients were identified. Normal IgG4 levels were present in 85% of patients (254/298), while 15% (44/298) were elevated. The overall prevalence of AIP was 17% (52/298). The sensitivity and specificity of IgG4 for AIP was 67% and 96%, respectively; however, the PPV was only 80%, including a 9% occurrence of PDAC in patients with an elevated IgG4. CONCLUSION: In this study of selected patients who underwent IgG4 testing, 9% of elevated IgG4 patients had PDAC. The overreliance on IgG4 as diagnostic for AIP may lead to mis-diagnosis and delayed treatment for PDAC.